PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN DAN KUALITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH PADA BADAN SIBER DAN SANDI NEGARA - Sutrisno, Sutrisno; Astuti, Indri (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
The Government Accounting Standards become the benchmark in the preparation of government financial statements, so it is necessary to apply the appropriate accounting standards so that the financial reports generated can be used correctly. The 2019 Cybersecurity and National Security Agency (BSSN) Financial Report has received a WDP (Rational With Exceptions) opinion because the BSSN has not fully implemented government accounting standards, constraints in compiling financial reports, or errors in the performance of agencies. The study entitled “Effects of Application of Government Accounting Standards and Quality of Financial Reporting on Accountability of Performance of Government Institutions BSSN”, aims to find out to what extent the application of government accounting standards and the quality of financial reporting influence on accountabilities of performance of government institutions based on the problems that arise.The field research was conducted using a quantitative approach and population research is the BSSN Financial Reporting Team. The study involved 33 respondents. This research data is collected using a questionnaire method. The author uses the double linear regression test and the hypothesis test with the SPSS27 program.The results of this study lead to the conclusion that the financial reporting quality variables have a significant influence on the accountability of the performance of government agencies. Financial reporting quality variable with a significance value of 0.012 0.05 and a tstatistic value of 2.261 ttable 2.042. Different from the variable application of government accounting standards that influences but is not significant on the accountability of the performance of government agencies because it has a significant value of 0.564 0.05, and the tstatistic value of -0,584ttable 2.042.